2007
DOI: 10.1097/iop.0b013e318070855b
|View full text |Cite
|
Sign up to set email alerts
|

Rhinocerebral Mucormycosis With Perineural Spread

Abstract: We describe the histopathologic findings of perineural invasion in orbital mucormycosis in a man with diabetes in ketoacidosis. Linear enhancement on MRI beginning at the orbital apex was correlated with fungal tracking of the trigeminal and lacrimal nerves. Mucormycosis can spread considerable distances from its primary focus of infection along peripheral nerves, a phenomenon that can be identified clinically with contrast-enhanced MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…Bone dehiscence proved to be a specific marker for AIFR (100% specificity) but has low sensitivity (35%), which agrees with previously reported data. 8 Because the fungi tend to spread through vascular channels or along nerves, [18][19][20][21] extension outside of the sinus frequently occurs in the absence of bone destruction. Therefore, bone destruction alone is not a useful exclusionary criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Bone dehiscence proved to be a specific marker for AIFR (100% specificity) but has low sensitivity (35%), which agrees with previously reported data. 8 Because the fungi tend to spread through vascular channels or along nerves, [18][19][20][21] extension outside of the sinus frequently occurs in the absence of bone destruction. Therefore, bone destruction alone is not a useful exclusionary criterion.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Perineural invasion was considered unusual but contrast-enhanced MRI studies have documented perineural invasion via the trigeminal nerve. [10][11][12][13] Cornley et al (2014) reported perineural invasion in 90% of biopsies that contained peripheral nerves. [17] In our series of invasive rhinocerebral mucormycosis, perineural invasion was histologically identified in 15/19 (72.1%) samples, where peripheral nerves were present in the biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Recent studies on imaging of rhinocerebral mucormycosis demonstrated spread of Mucorales species for considerable distance from its primary focus of infection along peripheral nerves. [13] Hence, we aim to study the histopathological features with particular emphasis on perineural invasion in invasive rhinocerebral mucormycosis.…”
Section: Introductionmentioning
confidence: 99%
“…[77,78] and Cunninghamella spp. [40,79]; one was culture negative [80] (Table 2). Sites involved included rhino-orbital (n = 8), abdominal/hepatic (n = 7), rhinocerebral (n = 6), pulmonary (n = 6), cutaneous (n = 5) and disseminated (n = 5).…”
Section: Case Seriesmentioning
confidence: 98%